2014
DOI: 10.1038/ng.3060
|View full text |Cite
|
Sign up to set email alerts
|

A common missense variant in NUDT15 confers susceptibility to thiopurine-induced leukopenia

Abstract: Thiopurine therapy, commonly used in autoimmune conditions, can be complicated by life-threatening leukopenia. This leukopenia is associated with genetic variation in TPMT (encoding thiopurine S-methyltransferase). Despite a lower frequency of TPMT mutations in Asians, the incidence of thiopurine-induced leukopenia is higher in Asians than in individuals of European descent. Here we performed an Immunochip-based 2-stage association study in 978 Korean subjects with Crohn’s disease treated with thiopurines. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
568
4
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 461 publications
(593 citation statements)
references
References 21 publications
16
568
4
5
Order By: Relevance
“…Determination of TPMT polymorphisms, therefore, has limited clinical benefits to children with ALL in most Asian countries. More recently, single nucleotide polymorphisms (SNPs) of inosine triphosphate pyrophosphohydrolase (ITPA) and nucleoside diphophate-linked moiety X-type motif 15 (NUDT15) have been shown to be associated with myelosuppression induced by 6-MP or other drugs in the thiopurine group, in both benign and malignant conditions [10][11][12][13][14] . We present data on the association between the ITPA c.94C>A (rs1127354) and NUDT15 c.415C>T (rs116855232) and 6-MP induced myelosuppression in our cohort of pediatric ALL children.…”
mentioning
confidence: 99%
“…Determination of TPMT polymorphisms, therefore, has limited clinical benefits to children with ALL in most Asian countries. More recently, single nucleotide polymorphisms (SNPs) of inosine triphosphate pyrophosphohydrolase (ITPA) and nucleoside diphophate-linked moiety X-type motif 15 (NUDT15) have been shown to be associated with myelosuppression induced by 6-MP or other drugs in the thiopurine group, in both benign and malignant conditions [10][11][12][13][14] . We present data on the association between the ITPA c.94C>A (rs1127354) and NUDT15 c.415C>T (rs116855232) and 6-MP induced myelosuppression in our cohort of pediatric ALL children.…”
mentioning
confidence: 99%
“…Asians are less likely (approximately 3%) to have TPMT mutation as compared with Caucasians (10%) 10. In Asians, NUDT‐15 mutation is more relevant for thiopurine‐induced toxicity than TPMT (risk allele frequency of 0.2% in Europeans,36 7.2% in Indians,15 8.5% in Thai,37 10.2–16.3% in Japanese,38 11.6% in Taiwanese,39 and 23.2% in Koreans14). Although it is said that Asian patients need a lower dose, almost half of our patients (31/57) on low dose and 5 of 17 on high dose (>2 mg/kg body weight) had subtherapeutic level.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the role of TPMT mutation may not be very relevant amongst Asians. Recently, nucleoside diphosphate‐linked moiety X‐type (NUDT‐15) genetic variant has been found to be significantly associated with thiopurine toxicity amongst Asians 14, 15…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies have extended these associations with variants in the HLA associated with the development of pancreatitis aft er thiopurine exposure ( 79 ). Another study demonstrated that the NUDT15 gene harbors a polymorphism associated with risk of bone marrow toxicity in a Korean population ( 80 ).…”
Section: Genetic Associations With Non-response To or Toxicity Frommentioning
confidence: 99%